ChemInform Abstract: Highly Enantioselective Sulfa‐Michael Addition Reactions Using N‐Heterocyclic Carbene as a Non‐covalent Organocatalyst. Issue 43 (October 2015) - Chen, Jiean; Meng, Sixuan; Wang, Leming; Tang, Hongmei; Huang, Yong
Abstract A triazolium salt derived NHC serves as an excellent Broensted base to promote the enantioselective carbon‐sulfur bond formation in the asymmetric sulfa‐Michael addition.